Regioselective Hydrogenation of a 60-Carbon Nanographene Molecule toward a Circumbiphenyl Core - Yao, Xuelin (J Am Chem Soc, 2019)
[Image: see text] Regioselective peripheral hydrogenation of a nanographene molecule with 60 contiguous sp(2) carbons provides unprecedented access to peralkylated circumbiphenyl (1). Conversion to the circumbiphenyl core structure was unambiguously validated by MALDI-TOF mass spectrometry, NMR, FT-IR, and Raman spectroscopy. UV–vis absorption spectra and DFT calculations demonstrated the significant change of the optoelectronic properties upon peripheral hydrogenation. Stimulated emission from 1, observed via ultrafast transient absorption measurements, indicates potential as an optical gain material.